Postmortem retrieval analysis of canine total hip arthroplasty - Skurla, Carolyn Patlovany, author; James, Susan, advisor; Radford, Don, committee member; Wheeler, Donna, committee member; Pluhar, Elizabeth, committee member (Colorado State University. Libraries, 2002)
With the aging of the human population in the United States comes a demand for increasingly advanced medical care options for the elderly. The average number of total hip arthroplasties (THAs) performed each year in the United States has increased from 204,000 in 1988 to 249,000 in 1995 with an estimated increase to 359,000 by 2030. The economic impact of THAs in the United States was estimated at $3.7 billion in 1995, and that figure will continue to increase.

The dog is commonly used as an animal model in human orthopaedic prosthetic development. In addition. THAs are performed clinically in dogs to treat diseased joints, alleviate pain, and increase function. This procedure has been performed at the Colorado State University Veterinary Teaching Hospital for over 20 years, but the long-term clinical performance of cemented THA in dogs was unknown.

This dissertation research involved performing engineering analysis on canine THA implants that had been implanted in client-owned dogs and were retrieved postmortem with the dual goal of improving our understanding of the dog as a model for human THA and of improving the clinical success of canine THA. Much has been learned about the performance and failure mechanisms of THAs in humans through postmortem retrieval studies, and that knowledge could not be gained in any other way.

The femoral and acetabular components were mechanically tested to assess the stability of the implant within the bone and the bone cement. The quality of the femoral cement mantle was assessed using radiographs of the intact and sliced femora. The acetabular components, made of ultra high molecular weight polyethylene (UHMWPE), were measured for volumetric wear and graded for types and location of damage to the UHMWPE. Wear debris was isolated from soft tissues surrounding the joint. The results of this study were also compared with similar findings in human postmortem retrieval studies in order to assess whether THA implants wear and fail by similar mechanisms in humans and dogs.

The incidence of aseptic loosening was alarmingly high for both the femoral and acetabular components in the dog with more than half of all components being loose. Surprisingly, the prostheses that had been implanted in dogs with bilateral THA tended to perform better than those implanted in dogs with unilateral THA. Just as human postmortem studies led to changes in human THA surgical technique, the results of this dissertation research are already leading to changes in the surgical paradigm for veterinary orthopedic surgeons across the country.
Keywords: biomedical research; mechanical engineering; biomedical engineering